Epidemiology of shoulder surgery among professional baseball players - Chalmers, P. N.; Erickson, B. J.; D`Angelo, J.; Ma, K.; Romeo, A. A. (The American Journal of Sports Medicine, 2019)
Background: Injuries remain a significant problem for professional baseball players. There is little information regarding the incidence and outcomes of shoulder surgical procedures among these athletes. Purpose/Hypothesis: To report the incidence, pathology, procedure type, demographics, and return-to-sport (RTS) rate of shoulder surgery among Major League Baseball (MLB) players. Most shoulder procedures would be performed on pitchers with a history of injury; the labrum would be the most commonly involved; and that the RTS rate would be >50%. Study Design: Descriptive epidemiology study. Methods: All MLB players who underwent surgery between 2012 and 2016 were identified from a database prospectively maintained by MLB. Demographic information and details regarding the procedure were recorded and RTS rates determined. Only those players with a minimum 2-year follow-up were included. Results: There were 581 shoulder procedures performed (542 players; pitchers, 60%; incidence, 1.48%). Overall, 19% of surgical procedures were performed on major league players and 81% on minor league players. Most players were between 20 and 25 years old. The majority of procedures were performed on the posterior and anterior labrum. Of these, 67% involved labral repair. Within rotator cuff surgery, 84% involved debridement; most tears were articular sided (87%); and 75% involved the supraspinatus. Overall, 11% of players had prior shoulder surgery, and 76% spent time on the disabled list before surgery. The overall rate of RTS was 63%. Of those who returned, 86% returned to at least the same level of play or higher as before surgery. Of those who returned to their prior level of play, 73% later ascended to a higher level of play or could not ascend to a higher level because they were already in the majors. Conclusion: Shoulder surgery is uncommon among professional baseball players. Of those players who require surgery, the majority are pitchers and minor league players. Most procedures involve the labrum. Rotator cuff tears are mostly articular-sided supraspinatus tears. The overall RTS rate is 63%. Of those who return, 86% are able to return to the same or higher level of play as before surgery.